Strategies Used by High, Medium and Low Achieving EFL Students in Learning English - PUTRA, AZIZ RAHMAN; PRADANA, AMI (Linguists : Journal of Linguistics and Language Teaching, 2023)
As an international language whose role and use are dominant in various aspects in this era of globalization, English is suitable to be used as the main provision for students to support their academics and careers. Therefore, it is very important to analyse the English learning Strategies applied by students so that learning has appropriate results. The Objectives of this research are to describe the types of English learning strategies used by high, medium, and low achieving students at Dehasen University Bengkulu, and to find out whether there are any differences in the use of English learning strategies among three groups. This was descriptive research. The population consisted of the students from two departments, namely physical education and Early Childhood Education year 2022-2023 were 159 students reported as students of the high (got A score), medium (got B score), and low achiever group (got C/D score). Purposive sampling technique was used. Purposive sampling technique was used. The instruments were students’ scores of English mastery and SILL questionnaire. Data were analysed by descriptive statistics by using SPSS 16 as well as in finding out the differences use of six categories of English learning strategies among the three groups. The results were as follows. All types of English learning strategies (memory, cognitive, compensation, metacognitive, affective, and social strategies) were used by all groups in the “moderate” category that were in the range 2.5 to 3.4. Metacognitive strategy was the strategy with the highest rank of use, whether for high which has a 3.37 mean score or medium achiever groups which has a 3.40 mean score. Meanwhile, memory strategy was the strategy with the highest rank of use for the low achiever group which has a 3.26. Furthermore, there were no differences in the use of English learning strategies among all groups, as can be seen from the result of two-way ANOVA data analysis